2018
DOI: 10.1128/jvi.00528-18
|View full text |Cite
|
Sign up to set email alerts
|

Evolution-Guided Structural and Functional Analyses of the HERC Family Reveal an Ancient Marine Origin and Determinants of Antiviral Activity

Abstract: In humans, homologous to the E6-AP carboxyl terminus (HECT) and regulator of chromosome condensation 1 (RCC1)-like domain-containing protein 5 (HERC5) is an interferon-induced protein that inhibits replication of evolutionarily diverse viruses, including human immunodeficiency virus type 1 (HIV-1). To better understand the origin, evolution, and function of HERC5, we performed phylogenetic, structural, and functional analyses of the entire human small-HERC family, which includes HERC3, HERC4, HERC5, and HERC6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 87 publications
4
39
0
Order By: Relevance
“…The latter were then correctly assigned to a different orthologous group than HERC5 . As previously reported in mammals ( 74 ), we identified strong evidence of positive selection on primate HERC6 (with five methods, Figure 2 ). This could mean that while both HERC5 and HERC6 have been evolving under positive selection in mammals, they have been subjected to different evolutionary constraints in primates, with a lower selective pressure on primate HERC5 vs HERC6 .…”
Section: Resultssupporting
confidence: 87%
“…The latter were then correctly assigned to a different orthologous group than HERC5 . As previously reported in mammals ( 74 ), we identified strong evidence of positive selection on primate HERC6 (with five methods, Figure 2 ). This could mean that while both HERC5 and HERC6 have been evolving under positive selection in mammals, they have been subjected to different evolutionary constraints in primates, with a lower selective pressure on primate HERC5 vs HERC6 .…”
Section: Resultssupporting
confidence: 87%
“…The latter were then correctly assigned to a different orthologous group than HERC5. As previously reported (Paparisto et al, 2018), we identified strong evidence of positive selection on HERC6 (with five methods, Figure 2). This could mean that while both HERC5 and HERC6 have been evolving under positive selection in mammals, they have been subjected to different evolutionary constraints in primates, with a lower selective pressure on primate HERC5 vs HERC6.…”
Section: Detection Of Ancestral Duplications Allows For Proper Assignsupporting
confidence: 88%
“…Low sample numbers precluded extensive validation in TCGA patient cohort; nevertheless a distinct alteration pattern of candidate genes was observed between HPV+ and HPV-cohorts of oropharyngeal cancers. A distinct set of prognosticators were identified for HPV+ and HPV-oropharyngeal cancers; ECHDC2, GGT6, HERC5 were showed to be associated with HPV+; HERC5 has a known anti-viral activity [78] [79] and its possible role in HNSCC HPV associated cancer is yet to be studied. On the other hand alterations in GRB10, EMILIN1, FNDC1, FOXF2 and HLX, determined poor prognosis in the HPV-cohort; this subset is involved in multiple carcinogenic processes in different solid tumors [80] [85].…”
Section: Discussionmentioning
confidence: 99%